1989
DOI: 10.1172/jci113978
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of early ventricular fibrillation by inhibition of acylcarnitine accumulation.

Abstract: Hypoxia in isolated myocytes results in accumulation of longchain acylcarnitines (LCA) in sarcolemma. nhibition of carnitine acyltransferase I (CAT-I) with sodium 2-15-(4-chlorophenyl)-pentyll-oxirane-2-carboxylate (POCA) prevents both the accumulation of LCA in the sarcolemma and the initial electrophysiologic derangements associated with hypoxia. Another amphiphilic metabolite, lysophosphatidylcholine (LPC), accumulates in the ischemic heart in vivo, in part because of inhibition of its catabolism by accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(67 citation statements)
references
References 45 publications
2
65
0
Order By: Relevance
“…The impaired long-chain fatty acid 13-oxidation activity in the patients would cause the shortage of energy owing to the inadequate muscle fat utilization and the deficient production of ketone bodies, normally the preferential fuel for myocardium and skeletal muscle. It would also cause accumulation of long-chain triglycerides and long-chain acylcarnitines, which may be toxic to cardiac muscle (43). These unfavorable factors may relate to the occurrence of cardiac diseases such as arrhythmia, cardiomegaly, and cardiomyopathy, and muscular disorders such as episodic muscle pain, rhabdomyolysis, and progressive muscular weakness.…”
Section: Resultsmentioning
confidence: 99%
“…The impaired long-chain fatty acid 13-oxidation activity in the patients would cause the shortage of energy owing to the inadequate muscle fat utilization and the deficient production of ketone bodies, normally the preferential fuel for myocardium and skeletal muscle. It would also cause accumulation of long-chain triglycerides and long-chain acylcarnitines, which may be toxic to cardiac muscle (43). These unfavorable factors may relate to the occurrence of cardiac diseases such as arrhythmia, cardiomegaly, and cardiomyopathy, and muscular disorders such as episodic muscle pain, rhabdomyolysis, and progressive muscular weakness.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, under limited oxygen availability, reduced cardiac mitochondrial ␤-oxidation predisposes to the accumulation of upstream extramitochondrial LCFA intermediates, such as long-chain acylcarnitine (LCAC), the product of the reaction catalyzed by M-CPT I. LCACs have been demonstrated to impair cardiac function through effects on cellular coupling, ion channel function, and sodium/potassium ATPase activity (36 -38). Previous studies (38) have shown that pharmacologic inhibition of LCAC accumulation in cells subjected to hypoxia prevents electrophysiologic derangements and improves cell survival. Given that CPT I catalyzes a rate-limiting step in mitochondrial FAO, down-regulation of M-CPT I expression would lead to a reduction of substrate flux into reactive oxygen species and LCACgenerating mitochondrial pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Second, administration of 5 pM palmitoyl-L-carnitine may inflict damage to the heart to an extent similar to that induced by ischemia in terms of tissue accumulation of long-chain acylcarnitines (8). Last, 5 pM palmitoyl-L carnitine produces not only mechanical dysfunction and energy deficiency but also membrane damage (8), and it induces electrophysiological alterations (1,3) in the heart. We observed that palmitoyl-L-carnitine produced mechanical dysfunction (as evidenced by an increase in LVEDP and a decrease in LVDP) and metabolic damage (as evidenced by a decrease in the tissue ATP level and an increase in the tissue AMP level).…”
Section: Discussionmentioning
confidence: 99%